Dilemas modernos. Tomo I : el proyecto urbano en Montevideo y la costa balnearia - Articardi, Juan (Montevideo, Uruguay : CSIC, Universidad de la República Uruguay, 2016)
Analysis of the the incorporation of the ideas of modern urbanism in Uruguay, particularly in the city of Montevideo in the first half of the 20th century, including Le Corbusier's, Plan for Montevideoʺ and its consequent progress and obstacles. The edition also explores the celebration of the futureʺ in which the Plan for the Centenary of Montevideo was developed, a territorial expansion that included the design of strategies for the urbanization of coastal areas which characterize and define the promenade of Montevideo and the whole set of projects of modern resorts.
TOMO 2: Parte IV. La capital -- Parte V. El territorio expandido -- Anexo: Le Corbusier -- Recorridos conceptuales hacia el "Sur", Massilla, 14 de septiembre, 1929.
Incluye referencias bibliográficas.
In Spanish, with an abstract and introduction in English.
Descripción basada en metadatos suministrados por el editor y otras fuentes.
Recurso electrónico. Santa Fe, Arg.: elibro, 2020. Disponible vía World Wide Web. El acceso puede estar limitado para las bibliotecas afiliadas a elibro.
Keywords: Le Corbusier, -- 1887-1965 -- Influence; Le Corbusier, -- 1887-1965 -- Influencia; Renovación urbana -- Uruguay -- Montevideo -- Historia -- Siglo XX; Urbanismo -- Uruguay -- Montevideo -- Historia -- Siglo XX; Urbanización -- Uruguay -- Historia -- Siglo XX; Urban renewal -- Uruguay -- Montevideo -- History -- 20th century; City planning -- Uruguay -- Montevideo -- History -- 20th century; Urbanization -- Uruguay -- History -- 20th century; Libros electrónicos.